Myeloid Cells as Targets for Therapy in Solid Tumors. Issue 4 (July 2015) - Cotechini, Tiziana; Medler, Terry R.; Coussens, Lisa M.
<x xml:space="preserve">Abstract</x> Abstract It is well established that cancer development ensues based on reciprocal interactions between genomically altered neoplastic cells and diverse populations of recruited "host" cells co-opted to support malignant progression. Among the host cells recruited into tumor microenvironments, several subtypes of myeloid cells, including macrophages, monocytes, dendritic cells, and granulocytes contribute to tumor development by providing tumor-promoting factors as well as a spectrum of molecules that suppress cytotoxic activities of T lymphocytes. Based on compelling preclinical data revealing that inhibition of critical myeloid-based programs leads to tumor suppression, novel immune-based therapies and approaches are now entering the clinic for evaluation. This review discusses mechanisms underlying protumorigenic programming of myeloid cells and discusses how targeting of these has potential to attenuate solid tumor progression via the induction and of mobilization CD8+ cytotoxic T cell immunity.